The Impact Of Changes In Needs Analysis In English Learning Curriculum Development - Kholida Ziya; Rahmadi Nirwanto; Zaitun Qamariah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the impact of changes in needs analysis on the development of English language learning curriculum. Needs analysis is an important process in designing a curriculum that is responsive to learners' needs. However, the needs of English language learners continue to evolve with changes in time, technology, and global demands. Therefore, changes in needs analysis are necessary to ensure that the English language learning curriculum remains relevant and effective. In studying the impact of changes in needs analysis on curriculum development in English language learning, the researcher will conduct a comprehensive search of academic databases, educational journals, conference proceedings, and other reputable sources. The search will be focused on finding relevant studies, theories, and models related to needs analysis, curriculum development, and English language learning. The results of the study indicate that changes in needs analysis have a significant impact on the development of English language learning curriculum. Some of these impacts include emphasizing more authentic communication skills, increasing the use of technology in learning, the need for cross-cultural skills, and emphasizing professional skills relevant to the workplace. This study concludes that changes in needs analysis are an important step in developing a responsive and effective English language learning curriculum. By considering changes in learners' needs, the curriculum can be adjusted to provide a more relevant and beneficial learning experience. Therefore, curriculum developers and education policymakers need to continuously monitor changes in learners' needs and make necessary adjustments in the development of the English language learning curriculum.